ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGALOKASIAN BELANJA MODAL - Nuzana, Merizal; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out the influence of Local Own-Source Revenue (PAD), and general allocation fund (DAU), Special Allocation Fund (DAK), and Profit Sharing Fund (DBH), dan Financing Surplus (SiLPA) to the capital expenditure (BM). The population of this research is all districts and cities in East Java which consist of 29 districts and 9 cities. The sample collection technique has been done by using purposive sampling. The research data is the secondary data in the form of Regional Government Budget (APBD) realization statement of East Java Province in 2012-2014 fiscal years. The hypothesis test has been done by using multiple linear regressions analysis. Based on the result of this research, it shows that the local own source revenue (PAD) has influence to the Belanja Modal (BM); DAU has negative influence to the BM; DAK does not have any influence to the BM; DBH has negative influence to the BM; and SiLPA does not have any influence to the BM.Keywords: Local Own-Source Revenue (PAD), general allocation fund (DAU), Profit Shring Fund (DBH), Financing Surplus (SiLPA), capital expenditure (BM).